The footwear sector in El Restrepo neighborhood in Bogota. A case study in the light of local production systems - Forero, Jesús David (Universidad de La Salle. Revistas. Equidad & Desarrollo., 2014)
This article presents the results of an investigation focused on the elaboration of an assessment of the economic situation of the footwear production and marketing agglomeration in El Restrepo neighborhood, located in Bogota. Such assessment was made based on the gathering, management, and analysis of qualitative and quantitative information raised from interviews and surveys made to businessmen in the area, and through consultation with unions and public entities involved in the activity of this agglomeration. The theoretical contextualization of the concept of local productive system is presented; then, the footwear industry is characterized, first addressing the international and then the national sphere. The agglomeration studied is highlighted; then, the methodology used for collecting and processing information in the fieldwork is presented, as well as the results obtained. Finally, the conclusions are presented.